Le Harcèlement Verbal (Pelecehan Verbal) dalam Film La Grande Classe Karya Remy Four dan Julien War - Lovenia Aveindra Krishanova; Dewi, Evi Rosyani; Lustyantie, Ninuk (Franconesia, 2024)
This study aims to describe verbal bullying in the Back To School film by Rémy Four and Julien War. The approach used is a qualitative approach by applying the content analysis method followed by the documentation study method as a data collection technique. In this research, the data analysis process follows the approach proposed by Miles et al. (2014), which involves the stages of data condensation or reduction, data display or presentation, and conclusion drawing or verification. The research stages, as described by Mahsun (2017), involve pre-research, conducting research, and writing a research report. Pre-research includes determining the research focus, problem formulation, theory, data sources, and research methods. Followed by the collection of research data, which involves words, phrases, and sentences in the film, then analyzed based on Fraisse's theory (2015). The results showed that there were 21 findings of verbal bullying in the movie.